Nurses Self-Perception about their Public Image at Public hospitals Pakistan (Journal of Medical & Health Sciences Review, 2025)
Objective: The purpose of the study was to explore and describe the diploma-BSN-prepared nurses’ self-perception about their public image in the city of Sindh, PakistanStudy Design: This Study was conducted through Cross-Sectional Quantitative Design.Material & Methods: A convenient sample of 94 diploma-BSN-based prepared nurses from five public hospitals was selected. Data were collected using the standardized Porter Nursing Image Scale and a self-developed demographic tool.Result: The perception of their public Image was ranked positive by the participants but differed in degree by three components of the tool.Conclusion: Efforts to understand and to enhance the image of the nursing profession are linked with better quality patient care, improved job satisfaction, and also linked with better quality patient care.